Keadaan Gizi Dan Faktor Determinan Kegemukan Pada Wanita Di Riau - Ikasarie Zamora; Dedi Parlaungan; Heryudarini Harahap (Jurnal Kebijakan Pembangunan dan Inovasi, 2016)
The data used in this analysis was Basic Health Research data in 2013 from the Riau Province. The population was women aged 15-49 that was interviewed in Riau Province. Samples were women, with the inclusion criteria 1) was not pregnant, and 2) had weight and height data. The total sample was 1,612,942 women. The objectives of this analysis were 1) to study the nutritional status situation of women, 2) to study the determinants factors of overweight in Riau. The prevalence of wasting and overweight in women aged 15-49 years in Riau Province, respectively 9.7% and 28.3%. The prevalence of overweight women was the highest in Siak district, namely 41.0%, and the lowest in Indragiri Hilir which was 20.6%. The prevalence of underweight women was the highest in Indragiri Hilir which was 16.3% and the lowest in Pekanbaru, namely 6.0%. The districts with prevalence of overweight higher than the prevalence of Riau Province were Kuantan Singingi, Pelelawan, Siak, Rokan Hulu, Bengkalis and Rokan Hilir. The districts with prevalence of wasting higher than the prevalence of Riau Province were Kuantan Singingi, Indragiri Hulu, Indragiri Hilir, Rokan Hulu, Rokan Hilir, and Meranti Islands. Determinant factors of women overweight in Riau Province were age, location of the district, frequency of fatty foods consumption, frequency of flavorings consumption, hormonal contraceptive and ownership of goods. Women that had more risk for becoming overweight were older women, women who lived in coastal areas, women who ate fatty foods or flavorings ≥ 1 times/day, women who use hormonal birth control and women with higher ownership.